Ethnoscience Study for Science Education Through The Process of Making Sopi Timor from Gewang Sap (Corypha utan Lamk.) - Nabuasa, Desi Aryanti; Sriyati, Siti; Liliawati, Winny (FKIP ULM, 2024)
The Gewang plant (Corypha utan Lamk) is an endemic plant that grows in the dominant vegetation of Timor Tengah Selatan (South Central Timor Regency). Nira is obtained from the gewang tree (Corypha utan Lamk) by inserting the what flower stems and then stored in a container for further fermentation with a mixture of red oak (Saccharum officinarum Linn), the hanging roots of the chickpeas (Ficus benjamina), the stems of the schleichera (Schleichera oleosa), the stem of the beetle (Ziziphus mauritiana L.), and the forest stems. (Piper aduncum L.). This study aims to study and describe the process of making sopi timor and analyze the scientific concepts that exist in the process. Based on the results of the study of the production of this sopi timor, public knowledge of fermentation and separation of solutions can be used as one of the materials to teach science content in the classroom with a local cultural approach. In the relationship between ESD and a Merdeka curriculum, there is a similar pattern of teachers taking a role in studying science in a contextual way that can be sourced from local cultures. It is intended for students to engage in meaningful learning processes because the context of their learning is related to their daily lives. The results of this research can be used as recommendations in context-based chemistry, biology, and physics learning in accordance with the culture in the South Central Timor Regency.